Bioethics education in Nigeria and West Africa: historical beginnings and impacts. Issue 2 (1st October 2016) - Ewuoso, Olukunle Cornelius
ABSTRACT: This study examines the historical beginnings of Bioethics in Nigeria and West Africa. Specifically, it highlights the major events that shaped the progress of Bioethics in Nigeria and West Africa, and evaluate the impacts Bioethics has had on the region. In the final analysis, this study makes recommendations regarding how advanced institutes can complement the efforts of bioethicists in West African Countries. West African Bioethics (WAB) Training Programs have significantly contributed to the pool of competent bioethicists, academics, health professionals and ethics committee members with requisite knowledge to design, evaluate, monitor, conduct and report studies without misconduct. There is still much, however, that remains to be done. Nevertheless, advanced Bioethics and biomedical institutes can take advantage of the accomplishments achieved so far, by helping to strengthen the WAB Training Programs through fellowships, exchange programs or other additional educational programs.